Managing Intergenerational Communication Gaps in The Malaysian Service Industry: Pathways to Improved Customer Experience - Krystalyn, Ericka; Omar, Nurul Nisa (Tropical Scientific Journal, 2026)
Objective: This conceptual paper develops an integrated framework to address intergenerational communication gaps within Malaysia’s service industry and their impact on customer experience (CX). Method: Drawing on a thematic synthesis of recent literature (2019–2025), the study integrates Generational Cohort Theory (GCT), Communication Accommodation Theory (CAT), and Organisational Control Theory (OCT) to construct a multi-level explanatory model. Findings: The proposed framework positions generational cohort traits as antecedents influencing communication accommodation behaviours, with organisational control systems acting as contextual moderators shaping communication climate. Communication accommodation serves as a mediating mechanism linking intergenerational interaction to CX outcomes, particularly customer satisfaction, trust, and loyalty. The model highlights how supportive control climates enhance communicative flexibility, while rigid structures may suppress adaptive behaviours, especially among Gen Z employees. Originality: This study contributes to Malaysian service-sector literature by integrating interpersonal and structural perspectives within a culturally grounded framework. The model offers practical guidance for HR policies, communication training, and service excellence strategies in multigenerational workplaces.